Bamboo partition / Norashikin Kamarudin ... [et al.] - Kamarudin, Norashikin; Abdul Latif, Nur Hannam; Ahmad Zaki, Junaiza; Mat Dom, Muhamad Shalihin (2016)
Bamboo partition is important for element of ergonomic improvement in developing countries. It focuses interior, and also offer a higher look and additional valuable in the market and the suitability of material for produced bamboo partition using a simple design. The wall partition that made by recycle furnitures were produced, and the data were collected via survey form. The data were analyzed using SPSS based on questionnaire that had been distributed to 100 correspondents. Most 80% of the correspondents give positive response to the material used, suitability, portability, simple design and price. From this study, it can be concluded that bamboo partition can be accepted by all age level, gender and also a profession. Most of correspondent agreed that partition made by bamboo give the traditional view. Most of the correspondents agreed for this product that can give be commercialized in furniture industry.